Geometric Geoid Model Determination for Camp David Estate, Centenary City, Abakaliki, Ebonyi State - Onwuzuligbo, C. U.; Elebe, E. O. (Journal of Spatial Information Sciences, 2025)
The precision of height determination is essential for engineering and surveying applications. However, in many urbanizing areas in Nigeria, such as Camp David Estate, Abakaliki, there is no localized geoid model, which leads to vertical datum discrepancies and poor integration of GNSS-derived elevations. This study employs the GPS/levelling method to develop a geometric local geoid model tailored for Camp David Estate. Ellipsoidal heights were obtained via static GNSS observations, while orthometric heights were derived through precise spirit levelling. Geoid undulations were computed by subtracting orthometric heights from ellipsoidal heights, followed by polynomial surface modelling to construct the geoid model. The ellipsoidal heights ranged from 45.921 m to 59.150 m (mean = 53.76 m), and orthometric heights ranged from 24.49 m to 37.72 m (mean = 31.87 m). Geoid undulations were relatively uniform (mean = 21.4310 m, SD = 0.0028 m), indicating the reliability of the simple geoid model. Validation against EGM2008 revealed a consistent bias of -0.1898 m. These results confirm the suitability of the geometric method for localized geoid modelling in urban Nigerian settings. The derived model should be adopted for surveying and geospatial operations in the study area to enhance vertical accuracy.
Keywords: Geoid model; GNSS/levelling; Camp David Estate; orthometric height; EGM2008